DIGITAL MARKETING ANALYSIS ON INCREASING BRAND AWARENESS AND BRAND ENGAGEMENT OF THE CUBE HOTEL YOGYAKARTA - Afthoruddin, Muhammad Adib; Alldila Nadhira Ayu Setyaning (Finance : International Journal of Management Finance, 2025)
The Cube Hotel Yogyakarta faces challenges in optimizing social media utilization to support modern marketing strategies. The lack of effective social media use can hinder efforts to enhance brand awareness and brand engagement among consumers. In the digital era, digital marketing plays a crucial role in expanding reach and customer engagement, particularly through high quality visual content, direct audience interaction, and the use of social media features such as digital advertising and influencer collaborations. This study aims to analyze the role of digital marketing in increasing brand awareness and brand engagement while optimizing marketing strategies relevant to the target audience. The research findings indicate that a more targeted digital marketing strategy can enhance brand awareness and customer interaction, positively impacting The Cube Hotel's competitiveness and business growth. Therefore, to achieve more effective and sustainable marketing goals, The Cube Hotel needs to optimize social media use with a more strategic approach.